Y - 4x ≤ -6y - 4x ≤ -6
We add 6y and 4x to each equality
7y ≤ 0 ≤ 6y + 4x -6
Observing:
7y ≤ 0, we see that the values of y can be only negative or 0, not positive.
So we are left with (-2,-14) (-1,-9) (0,-5)
We check the second equality:
6y + 4x - 6 ≥ 0 for these 3
None of the inequalities satisfy the given expressions simultaneously.
Answer:
Personification
Explanation:
the author is referring to death as a character, which it is not
C! I took this test too. The answer is definitely C.
C. Haiku is the most reasonable answer